Penanaman Karakter Nilai Pancasila Dalam Mencegah Terjadinya Los Generation di Pondok Pesantren - Komang Sundara; Sri Solehah (CIVICUS : Pendidikan-Penelitian-Pengabdian Pendidikan Pancasila dan Kewarganegaraan, 2019)
Tujuan penelitian ini (1) untuk mengetahui implementasi nilai – nilai Pancasila untuk membentuk karakter anak, (2) untuk mengetahui hambatan – hambatan yang dialami dalam penananman nilai – nilai Pancasila, (3) untuk mengetahui sistem pngawasan dan sanksi terhadap penanaman karakter pada anak. Penelitian ini menggunakkan metode penelitian kualitatif - deskriptif dengan pendekatan fenomenologis dan teknik pengumpulan data menggunakan observasi,wawancara, dokumentasi,triangulasi. cara menentukkan informan dalam penelitian ini ialah dengan purposive sampling dan Snowball sampling,yang dianalisis melalui, reduksi data, penyajian data,dan menarik kesimpulan serta metode pengabsahan data menggunakkan uji kredibilitas. Hasil penelitian ini ialah (1) implementasi penanaman nilai – nilai Pancasila di pesantren secara substansi materi dalam penguatan karakter santri, penerapan metode contoh dan pembiasaan pada santri, cerminan nilai – nilai Pancasila yang disajikan pada form penilaian raport santri. (2) Hambatan yang di alami dalam penanaman nilai – nilai Pancasila kurangnya kerjasama dari pihak pesantren dan lembaga terkait, kurangnya dukungan orang tua , kurangnya pelatihan maupun sosialisasi mengenai, pengembangan metode belajar yang belum optimal serta pemberian contoh dari ust-ustadzah, jumlah santri dengan tenaga pengajar yang tidak sesuai. (3) Bentuk sistem pengawasan dan pemberian sanksi dalam penanaman nilai – nilai Pancasila ialah sistem pengawasan langsung dan tidak langsung yang dilakukan melalui koordinasi wali kelas, dengan para ustazah,koordinator TPA serta pimpinan pesantren. According to the law. National Education System No. 20 of 2003 Chapter II Article 3 reads "National Education aims:" To develop the potential of students to become human beings who believe in and fear God Almighty, noble,healthy,knowledgeable, competent, creative, independent, and become citizens who are democratic and responsible ".This study illustrates how to instill the values of Pancasila in the formation of children's character as an effort to prevent the occurrence of Lost Generation. The purpose of this study (1) is to find out the implementation of Pancasila values to form the character of children, (2) to find out the constraints experienced in the management of Pancasila values, (3) to find out the superintendence system and sanctions against the planting of characters in children. This study uses a qualitative-descriptive research method with a phenomenological approach and data collection techniques using observation, interviews, documentation, triangulation. the way to determine informants in this research is purposive sampling and snowball sampling, which are analyzed through data reduction, data presentation, and drawing conclusions and data validation methods using credibility tests. The results of this study are (1) the implementation of the planting of Pancasila values in pesantren is carried out by implementing the pesantren curriculum stated in the Minister of Religion Regulation No.13 of 2014 concerning Islamic religious education teaches material on moral education as a form of material substance in strengthening the character of students, the application of sample methods and habituation to students, a reflection of the values of Pancasila presented on the student report card assessment form. (2) Obstacles experienced in instilling Pancasila values, lack of cooperation from the pesantren and related institutions, lack of parental support, lack of training and socialization regarding, development of learning methods that are not optimal and giving examples of ust - ustazah, the number of students with unsuitable teaching staff. (3) The form of a system of supervision and sanction in instilling Pancasila values is a system of direct and indirect supervision carried out through the coordination of the homeroom teacher, with the Ustadzah, TPA coordinators and boarding school leaders.